Development of insecticide-incorporated knitted fabric having long-lasting efficiency. (January 2016) - Katiyar, Priyanka; Mishra, Shraddha; Singh, Dev; Chandra, Lal; Srivastava, Anurag; Saxena, Arvind K
Insecticide-incorporated knitted fabrics are used to provide long-term efficacy against mosquitoes. This article described the method for making insecticide-incorporated filaments by using bi-component-spinning technique having core-sheath morphology whereas deltamethrin has been incorporated in the sheath-containing high-density polyethylene. The concentration of the deltamethrin is varied from 0.25% to 0.75% to assess its impact on bioassay efficacy. The developed filaments subsequently converted into knitted structure and possess excellent insecticidal efficiency even after 20 wash cycles and therefore can be effectively used for the fabrication of knitted mosquito nets. The residual deltamethrin content was also evaluated after successive wash cycles.